2006
DOI: 10.1007/s11136-006-0032-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Continence in Patients with Spina Bifida

Abstract: Using generic HRQoL measures, urinary/faecal incontinence and their medical management may not play a determinant role in HRQoL of persons with SB. However many other factors affect HRQoL in these patients. A longitudinal study design is recommended to assess whether incontinence management is associated with improved HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 36 publications
5
72
0
1
Order By: Relevance
“…In Table II this study many participants reported ongoing transient and/or persistent physical and psychosocial morbidity, such as bowel and/or urinary dysfunction and psychosocial issues, consistent with other published reports (32,35,36). There is evidence that urinary and faecal incontinence not only interfere with everyday life, but are also associated with poorer self-concept, self-esteem and participation (educational achievement, employment, etc.)…”
Section: Discussionsupporting
confidence: 87%
“…In Table II this study many participants reported ongoing transient and/or persistent physical and psychosocial morbidity, such as bowel and/or urinary dysfunction and psychosocial issues, consistent with other published reports (32,35,36). There is evidence that urinary and faecal incontinence not only interfere with everyday life, but are also associated with poorer self-concept, self-esteem and participation (educational achievement, employment, etc.)…”
Section: Discussionsupporting
confidence: 87%
“…In this study many participants reported ongoing transient and/or persistent physical and psychosocial morbidity such as bowel and/or urinary dysfunction and psychosocial issues, consistent with other reports [28,31,32]. Further, cognitive impairments are common, with detrimental effect on their emotional health and coping ability [33].…”
Section: Discussionsupporting
confidence: 87%
“…The treatment group showed a significant reduction in bladder and bowel related disability and psychological distress, and improved QoL (and psychosocial gains) at 3-month follow-up. Participants in this study were similar to those in other studies in terms of age, gender, disease severity and treatment [26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 54%
“…[14][15][16] In contrast, research on QOL in adults with myelomeningocele has produced mixed findings (for a review, see Sawin and Bellin 17 ). Although some investigations endorse a heightened risk for poor overall and domain-specific dimensions of QOL in individuals with myelomeningocele compared with peer groups, 16,18 other studies revealed moderate to high levels of satisfaction with QOL in adolescents and young adults with myelomeningocele (see, for example, Leger 19 ) or found QOL scores within the average range. 20 Young females with myelomeningocele may be especially vulnerable to poor psychosocial outcomes owing to their double jeopardy status related to sex and disability.…”
mentioning
confidence: 99%